A and C are the correct statements when simplifying this expression.
A is correct because the first step in simplifying the expression is to distribute the -7 to both terms inside the parentheses. This results in -63x + 35.
C is correct because it correctly states the simplified expression after distributing the -7. The simplified expression is -63x - 35, not -63x + 35 as stated in options D and E.
Which two statements are correct when simplifying this expression?
−7(9x − 5)
Responses
A First, distribute −7.First, distribute −7.
B First, calculate −7 + (−5).First, calculate −7 + (−5).
C −7(9x −5) = −63x − 35.−7(9x −5) = −63x − 35.
D −7(9x −5) = −63x + 35.−7(9x −5) = −63x + 35.
E −7(9x −5) = 63x − 35.−7(9x −5) = 63x − 35.
1 answer